The study of lateral variability of Kockatea Shale across the Perth Basin: an integration of electrofacies and lithofacies characteristics - Jafary Dargahi, H.; Rezaee, M. Reza (Australian Petroleum Production and Exploration Association, 2014)
The recognition of distinct rock types through log responses, referred to as electrofacies, is a fundamental role in mapping stratigraphic units that do not have any specific geological description. Lateral variability within adjoining intervals is differentiated by studying lithological characteristics such as petrography and mineralogy acquired from visual core description. In non-cored wells electrofacies analysis, therefore, is the most reliable way in determining reservoir zonations. The electrofacies’ accuracy is critically important in defining potentially desirable rock types for shale gas reservoirs in non-cored intervals, which can be obtained through an analogy of well log responses in identical lithofacies within cored wells. Considering the complexity of making a final prediction due to the unavailability of different well logs covering the whole area, only the gamma-ray log is used in determining electrofacies patterns within the studied shale gas intervals. The electrofacies patterns within identified lithofacies have been studied for the Kockatea Shale, which presented analogous patterns for identical lithological facies. The similarity has allowed for the correlation of lithofacies in cored and non-cored wells, and the evaluation of lithofacies variability and development within various wells. The correlation of the defined electrofacies indicates facies changes across the basin in association with thickening of some lithofacies. The thickest part of the electrofacies is shown at the Dandaragan Trough and the Beagle Ridge. Some electrofacies, however, have disappeared in some parts of these areas, such as lithofacies E in the Beagle Ridge, which is partially replaced by electrofacies C.